2019
DOI: 10.21608/ijma.2019.12445.1002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of serum level of vitamin D on term neonates with early onset sepsis

Abstract: Background: Neonatal sepsis a major health challenge associated with major morbidity and mortality. Neonatal care improved recently. However, different challenges regarding management still exist. Vitamin D deficiencies was proposed as a predictor of neonatal sepsis. Objective: To highlight the impact of vitamin D levels on early onset sepsis in full term neonates. Methodology: This is a case control which carried out at the neonatal intensive care unit of Al-Azhar university hospital (Damietta), from March to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…This fact reveals the association between vitamin D deficiency and inflammation, infection, and septic shock [ 25 ]. The current study identified an association between low vitamin D levels and high neonatal serum CRP, in line with previous studies that found an inverse relationship between CRP levels in septic neonates and blood vitamin D levels [ 17 , 26 , 27 ]. While, Grzanka et al, concluded that there was no significant relationship between vitamin D concentrations and CRP and attributed this finding to the small sample size and single evaluation of vitamin D concentration [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This fact reveals the association between vitamin D deficiency and inflammation, infection, and septic shock [ 25 ]. The current study identified an association between low vitamin D levels and high neonatal serum CRP, in line with previous studies that found an inverse relationship between CRP levels in septic neonates and blood vitamin D levels [ 17 , 26 , 27 ]. While, Grzanka et al, concluded that there was no significant relationship between vitamin D concentrations and CRP and attributed this finding to the small sample size and single evaluation of vitamin D concentration [ 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…This result was consistent with other researches which concluded that full-term newborns with low serum vitamin D levels were more prone to the risk of infection [ 5 , 17 , 29 , 30 ]. According to Soliman et al, a multivariate logistic regression analysis used to predict neonatal sepsis showed that a decline in serum vitamin D levels was substantially related to the risk of sepsis in newborns [ 26 ]. Another study explained this association by the disruption of the macrophage function and the inflammatory cytokines generation that can result from a vitamin D deficit [ 7 ] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the bacteriological culture profile of patients is unrelated to vitamin D insufficiency. Serum vitamin D levels were shown to have a substantial negative link with CRP; significant positive relationships with Apgar score, haemoglobin concentration, and platelet count in a study of term newborns with early onset sepsis by Soliman et al (13) . Our findings were consistent with those of Mutlu et al (14) , who compared 25hydroxy Vitamin D levels in babies with pathologic and physiological hyperbilirubinemia and discovered that there are substantial disparities between the case and control groups.…”
Section: Discussionmentioning
confidence: 96%
“…The optimal cut off value of 25(OH)D in ROC analysis was revealed to be 15.45 ng/ml with 91.3% sensitivity and 71.7% specificity (AUC = 0.824, 95% confidence range 0.7370.912, p 0.001) for predicting LOS, which is consistent with the findings of Bilgin & Gonulal (12) . The ROC curve of blood vitamin D was also used to differentiate between septic and control groups in research by Soliman et al (13) . At a cutoff value of 18.75ng/ml, the AUC was 0.907, the sensitivity was 100%, the specificity was 80%, the PPV was 83.3%, the NPV was 100%, and the accuracy was 100%.90%.…”
Section: Discussionmentioning
confidence: 99%